Machinability studies on aluminium matrix nanocomposite under the influence of MQL. (2020) - Kannan, C.; Varun Chaitanya, C.H.; Padala, Dwarakesh; Reddy, Likithnath; Ramanujam, R.; Balan, A.S.S.
Abstract: The overwhelming rise in pollution led to the enforcement of stern measures to restrict certain techniques and served a path to the development of alternate methods. Although aluminium hybrid composites were significantly seen in automobile and aerospace industries due to their enhanced thermal and mechanical properties, its machining is proven to be challenging. In this study, squeeze cast cylindrical workpieces are made out of unreinforced aluminium alloy and aluminium alloy-based hybrid nanocomposite. They are machined by varying the cutting speed, feed rate and depth of cut under dry and minimum quantity lubrication environments. The impact on cutting forces, surface roughness and tool wear are observed and compared and presented in this study